1996
DOI: 10.1071/mf9960099
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine Ichthyoplankton Ecology in Relation to Hydrology and Zooplankton Dynamics in salt-wedge Estuary

Abstract: The ichthyoplankton assemblage of the Hopkins River estuary, Victoria, was dominated by estuarine taxa that included demersal (goby, gudgeon) and pelagic (black bream, estuary perch, anchovy) species. The two seasonal peaks in fish larvae abundance were related to ( 1 ) the springlsummer zooplankton increase that occurred after flooding of the estuary and was comprised predominantly of copepod nauplii, thereby providing a good prey field for very young fish larvae, and (2) the autumn zooplankton maxima, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 30 publications
5
59
1
Order By: Relevance
“…Newton 1996), the buoyancy of eggs and early stages (e.g. Mackenzie et al 2007), shifts in the amount and location of suitable spawning grounds (Nicholson et al 2008) and the movement patterns of fish (e.g.…”
Section: Freshwater Flow Estuarine Fishesmentioning
confidence: 99%
“…Newton 1996), the buoyancy of eggs and early stages (e.g. Mackenzie et al 2007), shifts in the amount and location of suitable spawning grounds (Nicholson et al 2008) and the movement patterns of fish (e.g.…”
Section: Freshwater Flow Estuarine Fishesmentioning
confidence: 99%
“…Black bream spawn from late winter to early summer in southern Australia, predominantly in salinities >10 (Newton 1996, Haddy & Pankhurst 1998, Walker & Neira 2001, Nicholson et al 2008. Laboratory studies have shown that egg survival and hatching is greatest in waters with salinities >10 (Haddy & Pankhurst 2000), and larvae in the laboratory have shown high levels of deformity at salinities <15 (Haddy & Pankhurst 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Similar suggestions have been made for sparids. For instance, for both Acanthopagrus butcheri (Newton 1996) and Calamus proridens (Dubovitsky 1977) spawning cues on cold water temperatures leading to larval production at the period of maximum plankton abundance. While it may be the case that the timing of spawning does lead to a match between larval production and plankton productivity, this seems likely to be incidental or of secondary importance in warm water sparids.…”
Section: Discussionmentioning
confidence: 99%